Is it possible to bring together pastoral youth service with the academic learning process? - Pedro Soto (Universidad Politécnica Salesiana, 2013)
Is it possible a dialogue between the dynamics of youth ministry and academic learning process. As animated by the adult personnel of the school helps to guarantee a correct initiation or pedagogy of the proper imprint in the academic world for the evangelizer, and involves students in the work of evangelization whereby they connect the four pillars of education treated in the Delors Report with the three levels of evangelization under the guidance of the Church. Youth ministry, which is an organized action of the Church, is carried out by young men and women who involve themselves with Jesus Christ and his message and become protagonists of a civilization of fraternity, thus fulfilling the mandate of Jesus: "Go into the whole world and proclaim the Gospel to every creature (Mk. 16, 15). When the school moves thus, it is to say that it becomes a school of "pastoral importance"; one that, despite difficulties encountered from the various points of view, employs stragies for inserting the seeds of the Gospel into different scholastic environments, which often results in high academic learning and at the same time a robust living of the values of the Gospel.